Application of photo-crosslinkable gelatin methacryloyl in wound healing - Zhang, Jinli; Liu, Changling; Li, Xiaojian; Liu, Zhihe; Zhang, Zhi (Frontiers in Bioengineering and Biotechnology, 2023)
Wound healing is a complex and coordinated biological process easily influenced by various internal and external factors. Hydrogels have immense practical importance in wound nursing because of their environmental moisturising, pain-relieving, and cooling effects. As photo-crosslinkable biomaterials, gelatine methacryloyl (GelMA) hydrogels exhibit substantial potential for tissue repair and reconstruction because of their tunable and beneficial properties. GelMA hydrogels have been extensively investigated as scaffolds for cell growth and drug release in various biomedical applications. They also hold great significance in wound healing because of their similarity to the components of the extracellular matrix of the skin and their favourable physicochemical properties. These hydrogels can promote wound healing and tissue remodelling by reducing inflammation, facilitating vascularisation, and supporting cell growth. In this study, we reviewed the applications of GelMA hydrogels in wound healing, including skin tissue engineering, wound dressing, and transdermal drug delivery. We aim to inspire further exploration of their potential for wound healing.